Faktor-faktor yang Mempengaruhi Penerapan Sistem Informasi Akuntansi Manajemen pada UMKM di Kabupaten Garut - Putri, Amelia; Nova Sofia Rachmadania; Novie Susanti Suseno (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2025)
When it comes to local economies, micro, small, and medium-sized enterprises (MSMEs) play a crucial role in creating jobs and generating tax money. Financial management and decision-making are two areas that management accounting information systems mostly seek to improve. This research aims to fill a gap in our understanding of what drives small and medium-sized enterprises (SMEs) in the Garut Region to use MAS. The Garut Cooperative Office-registered SMEs in the Garut Region were the primary subjects of this research. Researchers used a purposive sampling strategy to choose research participants. For this investigation, thirty samples were taken from MSMEs that had been in operation for more than two years. Researchers used traditional assumption testing and multiple linear regression to examine the data. While the research did find that accounting informing system usage was affected by education level, after adjusting for firm age and size, no influence was observed on management accounting informing system use. Micro, small, and medium-sized enterprises (MSMEs) are more likely to use a management accounting information system if employees have higher levels of education, the business is larger, and the organization is older. These linkages are illuminated by this research.